THE INFLUENCE OF E-COMMERCE ON THE DYNAMICS OF MAKASSAR CITY DEVELOPMENT PLANNING - Sri Hutami Adiningsih S; Ika Wisudawaty; Kurniawan Kurniawan (Universitas Ichsan Sidenreng Rappang, 2025)
The development of digital technology has significantly changed the consumption patterns of urban communities in Indonesia, including Makassar City. One of the latest innovations in e-commerce is livestream shopping, a form of online shopping that combines entertainment and real-time transactions. This study aims to analyze the influence of e-commerce livestream shopping on the dynamics of urban development planning, particularly in terms of spatial planning, community economic behavior, and the transformation of the retail sector in Makassar. A quantitative approach was used with survey methods and descriptive analysis of secondary data from various sources. The results show that the rise of livestream shopping activities has driven a shift in spatial functions from physical to digital, and demands new adaptations in urban infrastructure planning, such as internet connectivity and logistics. Furthermore, this phenomenon influences the consumption behavior and lifestyles of urban communities, which are increasingly digitally oriented. The implications of these findings demonstrate the importance of integrating digital planning into Makassar's city development policies to create an environment responsive to digitalization trends. Keywords: shopping, e-commerce, urban planning, digitalization.